Meta-Analysis of the Effect of Cognitive Activity Exercise on Independence Ability in Post-Stroke Patients - Aktovianta, Lukman; Murti, Bhisma; Adriani, Rita Benya (Indonesian Journal of Medicine, 2022)
Background: A stroke is an attack on the brain that occurs when the blood supply to part of the brain is blocked so that part of the brain becomes damaged and dies because it does not get nutritional intake. Cognitive exercise activities can maintain optimal blood flow and improve the delivery of nutrients to the brain. The study aims to analyze the effect of cognitive exercise activity on the independence ability in post-stroke patients.Subject and Method: The study was a meta-analysis with PICO as the following: Population: post-stroke patients. Intervention: cognitive exercise activity. Comparison: no cognitive exercise activity. Result: independence ability. The articles used in this study were obtained from three databases, namely Google Scholar, PubMed, and ScienceDirect. The keywords for searching for the articles were "cognitive exercise activity" AND "cognitive ability" AND "post-stroke". The included articles were full-text English versions with a randomized control trial study design from 2012 to 2022. The article selection was conducted using the PRISMA flow diagram. The articles were analyzed using the Review Manager 5.3 application.Results: A total of 9 case studies from Europe (Oxford, Sweden, United Kingdom), South America (Brazil), North America (Texas, Jamaica), Asia (Korea), and Africa (Egypt) were selected for systematic review and meta-analysis. It was discovered that cognitive exercise activity of 0.36 units increased independence ability in post-stroke patients compared to not obtaining cognitive exercise activities. Result statistically (SMD = 0.36; 95% CI = 0.19 to 0.54; p<0.001).Conclusion: Cognitive exercise activity increased independence ability in post-stroke patientsKeywords: cognitive exercise activity, cognitive ability, post-stroke.Correspondence: Lukman Aktovianta. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: lukman.aktovianta15@gmail.com. Mobile: +6285641434548.Indonesian Journal of Medicine (2022), 07(03): 350-359https://doi.org/10.26911/theijmed.2022.07.03.12